Case report: Therapy adherence, MTTP variants, and course of atheroma in two patients with HoFH on low-dose, long-term lomitapide therapy - Kayikcioglu, Meral; Ozkan, Hasan Selcuk; Yagmur, Burcu; Bayraktaroglu, Selen; Vardarli, Asli Tetik (Frontiers in Genetics, 2023)
Background Homozygous familial hypercholesterolemia (HoFH) is a rare and devastating genetic condition characterized by extremely elevated levels of low-density lipoprotein cholesterol (LDL-C) leading to increased risk of premature atherosclerosis. HoFH patients mostly present with mutations in LDLR, however, herein we present two cases with concomitant MTTP mutations, who showed different clinical courses and treatment adherence on long-term therapy with the new MTTP-inhibitor Lomitapide. Objectives Our aim was to present the possibility of preventing the progression of atherosclerotic burden with effective and safe LDL-C reduction in HoFH patients with low dose Lomitapide therapy and to emphasize the role of treatment adherence in therapy success. Methods We present two patients with phenotypically HoFH, a compound heterozygous female and a simple homozygous male, both with LDLR and additional MTTP mutations, who were treated with the MTTP-inhibiting agent lomitapide, with different treatment compliances. The role of impulsivity was investigated through Barratt Impulsivity Scale 11, and the extent of the atherosclerotic burden was followed up using coronary artery calcium scoring, echocardiographic and sonographic findings, and eventually through a strict follow-up of laboratory parameters. The patients were on Lomitapide respectively for 8 and 5 years with no adverse effects. Conclusions Low dose Lomitapide on top of standard lipid lowering therapy with decreased frequency of lipid apheresis, enabled the prevention of the progression of atherosclerotic burden if associated with good adherence to therapy. The cause of incompliance might be explained by the impulsive behavior of the patients and non-adherence to low-fat diet.